A Review of Stem Cell Therapy for Acquired Brain Injuries and Neurodegenerative Central Nervous System Diseases - Watanabe, Thomas K. (PM & R, 2018)
Cell-based therapies have been the subject of much discussion regarding their potential role in enhancing central nervous system function for a number of pathologic conditions. Much of the current research has been in preclinical trials, with clinical trials in the phase I or I/II stage. Nevertheless, there is considerable interest in the public about the potential regenerative role that stem cells may have in improving function for these neurologic conditions. This review will describe the different types of stem cells that are available, review their possible effects, and discuss some of the variables that investigators need to consider when designing their studies. Current clinical research in the areas of stroke, traumatic brain injury, and neurodegenerative diseases (amyotrophic lateral sclerosis and Parkinson disease) will be reviewed. As this article is aimed at a rehabilitation audience, outcome measures, and the role of concurrent rehabilitation therapies will also be mentioned.